ANALISIS WACANA MULTIMODAL PADA IKLAN KOMERSIAL DI MEDIA SOSIAL PENDEKATAN TEORI MICHELE ANSETY DAN GEOFF BULL - Insa, Jualita Makarima; Shofi, Moh. Shofiuddin (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
This study aims to analyze multimodal discourse in commercial advertisements on social media, specifically the Good Day Latte x BABYMONSTER and Frisian Flag advertisements. Using a descriptive qualitative method, data were collected through video and image observation from YouTube and Instagram. The analysis applies Michele Anstey and Geoff Bull’s semiotic systems theory, which includes linguistic, visual, audio, gestural, and spatial modes. The findings show that both advertisements successfully integrate multiple semiotic modes to construct persuasive messages. The Good Day Latte advertisement features mixed languages (English, Korean, Indonesian), cheerful visuals with animation, energetic Korean pop music, expressive gestures, and a warm spatial arrangement. Meanwhile, the Frisian Flag advertisement uses informal language, Islamic family visuals, nutritional infographics, warm background music, natural gestures, and spatial layouts emphasizing togetherness and the “100 Years Trusted” claim. This multimodal integration strengthens emotional engagement and conveys product messages relevant to Indonesian cultural contexts, such as Ramadan and Eid al-Fitr.